Combatting intergenerational effects of psychotrauma with multifamily therapy - Mooren, Trudy; van Ee, Elisa; Hein, Irma; Bala, Julia (Frontiers in Psychiatry, 2023)
There is growing evidence that parental trauma is associated with psychosocial disorders, externalizing, internalizing problems, and higher sensitivity to posttraumatic stress disorder (PTSD) in children. Recent research findings suggest multidimensional relational, psychological, and neurobiological interrelated pathways of intergenerational influence. Moreover, the intergenerational effects of parental trauma need to be understood within a broader systemic context, as a part of family adaptation. This article explores research findings and clinical practice to enhance our understanding of intergenerational processes and presents directions for therapeutic interventions. A trauma focused multi-family therapy, aiming to restrict the relational consequences of parental trauma and strengthen family resilience, is described. The proposition is that to facilitate and improve the quality of parent-child interaction in response to psychotrauma, fostering emotion regulation capacities and mentalization is crucial. These efforts offered through family group interventions may benefit various families coping with adversity in culturally diverse societies.